Studi Komparatif Struktural Objektif Novel Anak Bajang Menggiring Angin dan Ramayana - Eko Santosa; Lastini Lastini; Harun Yahya (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to describe and compare the literary structures of Sindhunata's novel Anak Bajang Menggiring Angin and S. Sularso's Ramayana using an objective-structural approach. The study's focus is on intrinsic factors, specifically themes and penokohan, as well as reflections of the social values of Jawa culture that are present in both karyas. This study uses a kualitatif deskriptif method with the content analysis technique applied to two novel texts as the primary data. The study's findings indicate that both karyas have a common interest in discussing traditional topics such as the relationship between kebaikan and kejahatan, cinta sejati, pengorbanan, and nilai kepemimpinan. However, there are differences in alur kelengkapan, narasi kedalaman, and tokoh penggambaran. Anak Bajang Menggiring Angin presents the Ramayana in a more precise and symbolic manner, while Sularso's version of the story emphasizes the traditional forms of ungkapan and Jawa symbols. The results of this study are presented in a clear and concise manner by comparing two contemporary adaptations of the classic Ramayana story with objective-structural analysis that has not yet been widely discussed. This study aims to shed light on how modern sastra might serve as a local reflection of culture through traditional epik.